Global nitrogen budgets in cereals: A 50-year assessment for maize, rice, and wheat production systems - Ladha, J.K.; Tirol-Padre, A.; Reddy, C.K.; Cassman, K.G.; Verma, Sudhir; Powlson, D.S.; van Kessel, C.; de B. Richter, Daniel; Chakraborty, Debashis; Pathak, Himanshu (Springer, 2016)
Industrially produced N-fertilizer is essential to the production of cereals that supports current and projected human populations. We constructed a top-down global N budget for maize, rice and wheat for a 50-year period (1961 to 2010). Cereals harvested a total of 1551 Tg of N, of which 48% was supplied through fertilizer-N and 4% came from net soil depletion. An estimated 48% (737 Tg) of crop N, equal to 29, 38 and 25 kg ha−1 yr−1for maize, rice and wheat, respectively, is contributed by sources other than fertilizer- or soil-N. Non-symbiotic N2fixation appears to be the major source of this N, which is 370 Tg or 24% of total N in the crop, corresponding to 13, 22 and 13 kg ha−1 yr−1for maize, rice and wheat, respectively. Manure (217 Tg or 14%) and atmospheric deposition (96 Tg or 6%) are the other sources of N. Crop residues and seed contribute marginally. Our scaling-down approach to estimate the contribution of non-symbiotic N2fixation is robust because it focuses on global quantities of N in sources and sinks that are easier to estimate, in contrast to estimating N losses per se, because losses are highly soil-, climate- and crop-specific.